PHYTOCHEMICAL ANALYSIS, ANTIOXIDANT AND ANTIMICROBIAL ACTIVITY OF GUIERA SENEGALENSIS METHANOLIC EXTRACT - J. M. , Abigail; H. M. , Adamu; D. E. A. , Boryo; A. A. , Mahmoud; A. , Kwaji (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2024)
Medicinal plants are widely used by the populace for their everyday health needs. The presence of phytochemical compounds is believed to be the basis of the observed pharmacological properties of medicinal plants. The aim of this research is to investigate the phytochemical constituents, antioxidants and antimicrobial activities of Guiera senegalensis (whole plant) plant. Phytochemical analysis (qualitative and quantitative) was carried out by following standard procedures. Free radical scavenging activity (DPPH) and ferric reducing antioxidant power (FRAP) were employed to determine the antioxidant activities of the methanol extracts of the plants, while paper disc agar diffusion method was used to determine the antimicrobial activity of the extracts. The result from the phytochemcal analysis revealed that the plant extract contains alkaloids, flavonoids, steroids, saponins, terpenoids, anthraquinones and tannins. Glycosides were not detected. The quantitative analysis results showed that, the plant extracts have appreciable amounts of phytocompounds with the highest value of 286.22 mgGAE/100 g total phenol. Extract showed high antioxidant activity of 84.15 % scavenging activity using DPPH and 13.05 % reducing power with FRAP. Results from the antimicrobial activity showed that, the plants extracts can inhibit bacteria growth of Escherichia coli, Shigella spp, Staphylococcus aureus, Staphylococcus epidermis, Streptococcus spp, Klebsiella pneumonia and Salmonella typhi. The highest inhibition zone of 43 mm at 500 µg/mL was observed for Streptococcus spp. and Shigella spp. Extracts exhibited lower zones of inhibition for antifungal activity. Consequently this study lends support to the therapeutic use of Guiera senegalensis in traditional medicine.